Enhancement of food waste thermophilic anaerobic digestion through synergistic effect with chicken manure. (May 2020) - Chuenchart, Wachiranon; Logan, Mohanakrishnan; Leelayouthayotin, Chirawit; Visvanathan, Chettiyappan
Abstract: Anaerobic co-digestion in thermophilic condition leads to efficient waste treatment and energy recovery through accelerated and enhanced synergism. The performance of anaerobic co-digestion of food waste with chicken manure was investigated for overcoming the challenges due to process inhibition during mono-digestion of food waste. The bench scale anaerobic Continuously Stirred Tank Reactor (CSTR) system with the working volume of 87 L in wet condition with 10% total solids content was used for this study. Though thermophilic food waste anaerobic digestion indicated high methane yield and solids reduction, the process stability was affected at higher loading. Whereas, the reduction in FOS/TAC value (the ratio of volatile fatty acids to total alkalinity) through co-digestion indicated the higher capacity for organic loading rate in the anaerobic co-digestion system due to synergistic effect of microorganisms, buffering capacity and nutrient balance by C/N adjustment in the feedstock. Moreover, the percentage increases of specific methane yields in co-digestion compared with mono-digestion was found to be 33.2%, 10.4%, 12.1% and 89.9% at organic loading rates (OLR) of 1, 2, 3 and 4 kg VS‧m −3 ‧d −1 respectively, as a consequence of the improvement in stability through co-digestion. Graphical abstract: Image 1 Highlights: Challenges in anaerobic mono digestion was addressed with co-digestion. Food waste digestion poses process inhibition due to acidification at higher loading. Higher methane yield and stability were observed in anaerobic co-digestion system. Co-digestion with chicken manure overcomes process inhibition by synergistic effect. Chicken manure increased buffer capacity and nutrient availability in co-digestion.